2017
DOI: 10.1126/science.aag3218
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the cyanobacterial circadian oscillator frozen in a fully assembled state

Abstract: Cyanobacteria have a robust circadian oscillator, known as the Kai system. Reconstituted from the purified protein components KaiC, KaiB, and KaiA, it can tick autonomously in the presence of adenosine 5'-triphosphate (ATP). The KaiC hexamers enter a natural 24-hour reaction cycle of autophosphorylation and assembly with KaiB and KaiA in numerous diverse forms. We describe the preparation of stoichiometrically well-defined assemblies of KaiCB and KaiCBA, as monitored by native mass spectrometry, allowing for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
147
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(152 citation statements)
references
References 51 publications
(47 reference statements)
5
147
0
Order By: Relevance
“…Altogether, KaiC hexamers phosphorylate and dephosphorylate rhythmically during the course of a day. Two very recent studies provide a structural basis for the dynamic assembly of clock proteins by using crystallography and NMR [32], and mass spectrometry and cryo-electron microscopy of the native proteins [33]. The binding of oxidized quinones to KaiA has been suggested to stop the clock directly by causing KaiA aggregation [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, KaiC hexamers phosphorylate and dephosphorylate rhythmically during the course of a day. Two very recent studies provide a structural basis for the dynamic assembly of clock proteins by using crystallography and NMR [32], and mass spectrometry and cryo-electron microscopy of the native proteins [33]. The binding of oxidized quinones to KaiA has been suggested to stop the clock directly by causing KaiA aggregation [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…We assume that KaiB can bind to only C1 in the BC state and that KaiA can bind strongly to the KaiB-C1 complex, which eventually results in the sequestration of KaiA from C2. Moreover, the conformational transition from BI to BC state is assumed to be promoted when C1 binds abundant ADP rather than ATP, as suggested experimentally [20,21,32,33]. Under this assumption, switching between phosphorylation and dephosphorylation is controlled by the ADP/ATP exchange in C1 because the exchange determines the amount of ADP in C1, which is the trigger of the conformational transition from BI to BC state.…”
Section: Model Setupmentioning
confidence: 99%
“…During the oscillation, C1 and C2 allosterically communicate and regulate the (dis)assembly of KaiA and KaiB through several domain-specific conformational transitions. For example, recent studies on the KaiABC complex [20,21] have revealed that KaiB can bind to an ADP-bound conformation of C1 [22]. On the other hand, C2 has the buried and exposed states of the C-terminal tail [14,15], and KaiA can bind only in the latter state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KaiB, on the other hand, inhibits KaiA activity 13,14 , which results in the dephosphorylation of C2. Specifically, after adequate phosphorylation of C2, KaiB binds to C1 and strongly sequesters KaiA from C2 by forming the C1-KaiB-KaiA complex 15 , which has recently been observed directly 16,17 .…”
Section: Introductionmentioning
confidence: 98%